The House as a Product - A. Vogler (Research in Architectural Engineering Series, 2016)
Industrialized housing has been a common phenomenon in the building industry since the industrial revolution; the casting of iron components enabled Victorian iron casters to prefabricate entire buildings and to export them to all British colonies. It got a second boost from Modernist architects like Ludwig Mies van der Rohe, Walter Gropius and Konrad Wachsmann; and a third boost in the US when the soldiers came back from the Second World War in 1945 and wanted to buy a ready-made house. In the later decades of the 20th century composite prototypes were built. Timber frame houses are extremely popular in low density areas worldwide. For densely populated areas housing is now firmly attached to reinforced concrete. The contracting industries have developed efficient building methods for the concrete structures on which separate systems of claddings are fixed to form a house. However, in the coming decades, designers, builders and scientists also have to keep the environment in mind, working with a minimal amount of materials, and for minimizing embodied energy and energy use. In the coming age minimal embodied energy and low ecological footprints are renewed values that will be added to energy-positive housing and that will have an influence on the building technology of the future. This will lead to a reformation of the building vocabulary. Other materials will have to be chosen and developed to function in building elements and components.